Does Background Is Important? Analysis of Demographic Characteristics to the Sports Entrepreneurial Intention - Mohamad Hasan Peymanfar; Mahdi Akbarian (Sports Business Journal)
Purpose: This research aims to identify and investigate the relationship between demographic characteristics and entrepreneurial intention of physical education and sports science students.Methodology: 391 participants from the students of the sports science faculty of the selected universities participated in the study were randomly selected. The quantitative method was used, and the six experts confirmed the validity of the questionnaire, And the reliability of the questionnaire was confirmed using Cronbach's alpha coefficient of 0.910. SPSS software was used to analyze the data.Findings: The study identified some main factors that increase people's willingness to be entrepreneurs. This study showed a significant relationship between the university of study, elite sports background, level of education, gender, parents' occupation, age, experience living abroad, and entrepreneurial intention. On the other hand, there is no relationship between marital status and having specialized skills concerning entrepreneurship intention, which indicates that just marital status and having technical skills cannot improve students' entrepreneurial intention.Originality: The entrepreneur is a combination of risk and willingness to succeed, but it is not easy to achieve due to the influence of the internal and external business environment. Therefore, this study was conducted to identify the main factors influencing people's willingness.